Monument on The Border: Preservation and Availability - Abrahamyan, Hamazasp (History and Culture, 2025)
After the 44-day Artsakh war and subsequent border changes, challenges arose regarding the preservation and accessibility of monuments near the border. To discuss the changes in the cultural landscape and the status of monuments in the border zone, we singled out the Goris region. In general, monuments can be divided into three main groups, according to their preservation problems and the type of accessibility: monuments that have passed into the territories of Azerbaijani control, monuments located in the neutral zone and/or near the border and without access, monuments close to the border and with access. In the case of these three groups of monuments, the problems of their preservation and accessibility are different. But, taking into account the possibility of border changes and military clashes, all monuments can be targeted or appear in the area of ​​possible new military operations. Thus, the condition of the monuments that play an important role in completing the cultural landscape of the border settlements has changed after the 2020-2022 Azerbaijani aggression, and this change is expressed in different ways in the case of different monuments. Among these monuments are the Bgheno Noravank, which occupies an important place in the cultural heritage of Armenia, Srnegtsi, the Melic palace of Khnatsakh, many khachkars, monasteries, churches, Melic palaces, rock-hewn complexes, burial grounds, settlements, cemeteries, monuments, etc.